The Rheological Characteristics of Dammar Mata Kuching - Chairul Umam, Azhar, Elida Purba (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
Rheology is already defined as the science of flow and deformation of matter. The purpose of rheology is to look at the relationships between stress and deformation of the material-marterial (non-Newtonian) in order to explain its mechanical properties. One of the ingredients that is often used as a basic material for making products is dammar. Dammar is a general term used to name a material in the form of natural resin which is the result of exudation of trees from the Dipterocarpaceae and Burseraccae families. This research uses raw materials dammar and toluene which are used to make a solution of dammar with the proportion of dammar: toluene, namely 50: 50, 40: 60, 35: 65, and 30: 70. Then the rheological analysis is analyzed by measuring the viscosity value, the shear rate. , and also its shear stress. The viscosity value increases with the greater the shear rate and the value of n (Flow Behavior index) is> 1, indicating that a solution of resin is a fluid with a type of dilatan fluid. Keywords: dammar, deformation, rheology, shear rate, shear stress.